2022
DOI: 10.3389/fonc.2022.848296
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles and Mechanisms of lncRNA FOXD3-AS1 in Human Diseases

Abstract: Numerous long noncoding RNAs (lncRNAs) have been identified as powerful regulators of human diseases. The lncRNA FOXD3-AS1 is a novel lncRNA that was recently shown to exert imperative roles in the initialization and progression of several diseases. Emerging studies have shown aberrant expression of FOXD3-AS1 and close correlation with pathophysiological traits of numerous diseases, particularly cancers. More importantly, FOXD3-AS1 was also found to ubiquitously impact a range of biological functions. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 176 publications
(255 reference statements)
0
10
0
1
Order By: Relevance
“… 36 FOXD3‐AS1 is strongly expressed in a range of disorders, including breast cancer, nasopharyngeal carcinoma, osteosarcoma, melanoma, and thyroid cancer. 37 Zheng et al 38 found that knocking down FOXD3‐AS1 prevented hypoxia‐induced cardiomyocyte damage by up‐regulating the cardioprotective molecule miR‐150‐5p. SLCO4A1‐AS1 is a protective factor for HNSCC prognosis and is significantly associated with overall patient survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 36 FOXD3‐AS1 is strongly expressed in a range of disorders, including breast cancer, nasopharyngeal carcinoma, osteosarcoma, melanoma, and thyroid cancer. 37 Zheng et al 38 found that knocking down FOXD3‐AS1 prevented hypoxia‐induced cardiomyocyte damage by up‐regulating the cardioprotective molecule miR‐150‐5p. SLCO4A1‐AS1 is a protective factor for HNSCC prognosis and is significantly associated with overall patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…FOXD2‐AS1 is elevated in HNSCC tissues and is a potential predictor of HNSCC in patients, promoting the proliferation of HNSCC cell lines 36 . FOXD3‐AS1 is strongly expressed in a range of disorders, including breast cancer, nasopharyngeal carcinoma, osteosarcoma, melanoma, and thyroid cancer 37 . Zheng et al 38 found that knocking down FOXD3‐AS1 prevented hypoxia‐induced cardiomyocyte damage by up‐regulating the cardioprotective molecule miR‐150‐5p.…”
Section: Discussionmentioning
confidence: 99%
“…FOXD3-AS1 has been shown to have predictive value and functional roles in various diseases, including breast cancer, cervical cancer, nasopharyngeal carcinoma, cerebral ischemia/reperfusion injury, cardiomyocyte injury, allergic rhinitis, and so on [ 15 – 17 , 27 , 28 ]. Furthermore, FOXD3-AS1 has been found in nuclear or cytoplasm fractions, and its molecular mechanisms include acting as competing endogenous RNA [ 15 , 29 ], acting as mediators for gene promotor loci and histone modification factor interaction [ 19 ], stimulating proteins expression [ 20 ], interacting and sequestering proteins, and so on [ 14 , 18 ]. In this study, we found that FOXD3-AS1 was upregulated in all primary subtypes of LC at an early stage and increased as the disease progressed.…”
Section: Discussionmentioning
confidence: 99%
“…[15-17, 27, 28]. Furthermore, FOXD3-AS1 has been found in nuclear or cytoplasm fractions, and its molecular mechanisms include acting as competing endogenous RNA [15,29], acting as mediators for gene promotor loci and histone modification factor interaction [19], stimulating proteins expression [20], interacting and sequestering proteins, and so on [14,18]. In this study, we found that FOXD3-AS1 was upregulated in all primary subtypes of LC at an early stage and increased as the disease progressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation